1942
DOI: 10.1021/ie50392a016
|View full text |Cite
|
Sign up to set email alerts
|

Heat Denaturation of Protein in Soybean Meal

Abstract: THE industrial significance of a study of the denaturation of soybean protein lies in the fact that denaturation is a factor to be considered in every commercial process to which the bean is subjected. It is of paramount importance in any process involving the preparation of a water-soluble soybean protein, and this importance is maintained in the possibility of preparing a chemically untreated yet insoluble soybean protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1947
1947
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 4 publications
(5 reference statements)
0
6
0
Order By: Relevance
“…The curves resembled those characteristic of autocatalytic reactions. Beckel, Bull, and Hopper (3) reported that solvent-extracted soybean heated at 120°and 0% relative humidity for 2.5 hours contained only 49% as much water-extractable protein as did unheated meal. HEATING…”
Section: I^hementioning
confidence: 99%
“…The curves resembled those characteristic of autocatalytic reactions. Beckel, Bull, and Hopper (3) reported that solvent-extracted soybean heated at 120°and 0% relative humidity for 2.5 hours contained only 49% as much water-extractable protein as did unheated meal. HEATING…”
Section: I^hementioning
confidence: 99%
“…However, Beckel et al found that denatured soy protein plasticized with formamide (a teratogen, unfortunately) could be successfully molded. 18 This material reportedly retained its strength and displayed little swelling or distortion when submerged in water for 48 hours and then dried. Thus, denatured, insoluble soy protein holds promise as a water-resistant plastic material.…”
Section: Protein-based Biopolymersmentioning
confidence: 93%
“…Demonstration that measurable amounts of lipid material remain in protein isolated from hexane-extracted soybean flakes suggests that oxidation of lipid components may be a factor in the flavor of soybean protein products (7). Removal of much of the flavor and lipid material by extraction of dehulled, defatted soybean flakes with alcohols supports this suggestion (8).…”
Section: Identification Of Flavor Componentsmentioning
confidence: 95%
“…Earlier we mentioned some studies involving extraction with alcoholic solvents. Alcoholic treatment does partly inactivate enzymes in soybeans and does remove substantial amounts of hpids and flavor (5,7,8,20). Alcohol suffers from some of the same disadvantages as cooking and steaming.…”
Section: Procedures For Removing Flavormentioning
confidence: 99%